2019
DOI: 10.1007/s11005-019-01217-4
|View full text |Cite
|
Sign up to set email alerts
|

On multiplicities of irreducibles in large tensor product of representations of simple Lie algebras

Abstract: In this paper we study the asymptotic of multiplicities of irreducible representations in large tensor products of finite dimensional representations of simple Lie algebras and their statistics with respect to Plancherel and character probability measures. We derive the asymptotic distribution of irreducible components for the Plancherel measure, generalizing results of Biane and Tate and Zelditch. We also derive the asymptotic of the character measure for generic parameters and an intermediate scaling in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…This result can be interpreted as a random walk with a critical drift [5]. Connection to random walks is easy to understand in the sl 2 -case for the probability measure defined on the weight diagram of N -th tensor power of fundamental representation L ω : p(λ) = dimV λ (dimL ω ) N , where dimV λ is the dimension of the weight subspace in the representation (L ω ) ⊗N .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result can be interpreted as a random walk with a critical drift [5]. Connection to random walks is easy to understand in the sl 2 -case for the probability measure defined on the weight diagram of N -th tensor power of fundamental representation L ω : p(λ) = dimV λ (dimL ω ) N , where dimV λ is the dimension of the weight subspace in the representation (L ω ) ⊗N .…”
Section: Discussionmentioning
confidence: 97%
“…The case g = so 2n+1 , N → ∞, n = const was studied in [3] and [4]. The central limit regime and the regime of large deviations for character measure (5), with n fixed, N → ∞, were considered in [5] by O.Postnova and N.Reshetikhin. They also suggested that in the regime near the boundary the character measure will converge to some Poisson type process.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [30] an asymptotic formula for tensor product decomposition coefficients was obtained. The character measure was studied in the case of Lie albegras of fixed rank n in the papers [26]. In a separate publication we will consider the limit n, N → ∞ for the character measure.…”
Section: Discussionmentioning
confidence: 99%
“…The asymptotic behavior of this measure was studied in three regimes: N → ∞ with n fixed, N → ∞, n → ∞ with N/n fixed and N, n → ∞ with N/n 2 fixed. The first case was studied [14] and later generalized to all simple Lie algebras in [25,26,30]. For the second case Kerov discovered that Vershik-Kerov-Logan-Shepp limit shape of Young diagrams with respect to the Plancherel measure on S N as N → ∞ also appears as the limit shape with respect to this measure.…”
Section: Introductionmentioning
confidence: 99%
“…In [23], Tate and Zelditch analysed the multiplicities in high tensor powers and proved a central limit theorem as well as large deviation results by relating them to the (much simpler) weight multiplicity asymptotics. Moving away from the tracial state to positive operators arising from the representation of the complexified group, Postnova and Reshetikhin [20] generalised these asymptotic formulas to character distributions.…”
Section: Introductionmentioning
confidence: 99%